Lavage through malpositioned nasogastric tube: a cause of concern - Takhar, Rajendra Prasad; Bunkar, Motilal; Arya, Savita; Saran, Rama Kishan (International Journal of Research in Medical Sciences, 2017)
Nasogastric tube (NGT) placement is a frequently used procedure in intensive care units either for enteral feeding or in cases of poisoning, where it is an important and emergent tool for gastric irrigation. Although, insertion of NGT has been pronounced as being easy and without risks, the increasing prevalence of the use of enteral feeding tubes during critical illness leads to the increased potential for malpositioning of a nasogastric tube. It is more hazardous if any therapeutic procedure has been performed through these malpositioned nasogastric tubes. Here, we are describing a unique case of malpositioning of nasogastric tube into left main bronchus in a case of unknown drug poisoning. The consequences of malposition of NGT, lavage through this NGT leading to grave respiratory complications and significance of a check x-ray chest following tube placement are discussed here.